Socially Responsible Investment (SRI) Attitude of Mutual Fund Investors in Nepal - Bajrachrya, Rajan Bilas; Samdani, G. L. (Nepal Journal of Multidisciplinary Research, 2021)
The study is to identify the influence of various demographic and other factors on the attitude of Nepalese mutual fund investors towards Socially Responsible Investment. A structured questionnaire was applied as a tool to collect primary data from the sample rural households. The sample size of 109 mutual fund investors is selected from Kathmandu Districts of Province three. The sampling procedure adopted in this study is Non probability convenient sampling. The descriptive research design is adopted in this research. It is found from the research that the age of the respondents has the considerable association with the factors considered for the investment decision. But the gender, educational qualification and the monthly income of the mutual fund investors has no relationship with the criteria for their investment decision.